2015
DOI: 10.1371/journal.pone.0141638
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Regular Participation in Sports Groups among Japanese Older Adults: JAGES Cross–Sectional Study

Abstract: BackgroundParticipation in a sports group is key for the prevention of incident functional disability. Little is known about the correlates of older adults’ participation in sports groups, although this could assist with the development of effective health strategies. The purpose of this study was to identify the demographic and biological, psychosocial, behavioral, social and cultural, and environmental correlates of sports group participation among Japanese older adults.MethodsData were obtained from the Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 33 publications
8
46
2
Order By: Relevance
“…The third is that we used combinations of two variable categories for “total frequency of exercise”, which may have resulted in a slight lack of accuracy. The fourth is that there may be a confounding effect from demographic and psychosocial factors related to exercising with others28, which we did not examine. The fifth is that the study was cross-sectional, and therefore cannot determine causal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The third is that we used combinations of two variable categories for “total frequency of exercise”, which may have resulted in a slight lack of accuracy. The fourth is that there may be a confounding effect from demographic and psychosocial factors related to exercising with others28, which we did not examine. The fifth is that the study was cross-sectional, and therefore cannot determine causal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…PrG and PuG have common related factors, such as better mental health for new participation and more intimate relationships with neighbors for new or continuous participation. Health status and social relationships are strongly related to sports group participation, and other longitudinal studies showed that social capital and social function affect engagement in volunteer work . Individuals who have good relationships with their neighbors are more likely to obtain information about social groups and to receive encouragement from neighbors to participate in such activities.…”
Section: Discussionmentioning
confidence: 96%
“…First, volunteer, hobby and sports groups were classified as private groups (PrG), as they comprise members who engage in specific activities and share common interests. According to previous studies, private groups have similar related factors of participation . Second, neighborhood associations and senior citizen clubs were categorized as public groups (PuG), as they are organized by local community members and offer multiple activities to enhance the lives of members.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations